I HAVE NOTHING TO DO WITH LANGUAGE TEACHING – LANGUAGE PRACTICES, IDEOLOGIES AND LANGUAGE MANAGEMENT IN EDUCATION - Lazdiņa, Sanita (Via Latgalica, 2016)
The aim of this article is to identify links observable in social practice between the process of multilingualism and the teaching of language and other subjects in school, as well as associated opportunities and models which are supported by the strengthening of interdisciplinary aspects.The article consists of five sections: the first two mainly theoretical, the last three – supported by empirical evidence. The first section is devoted to a theoretical explanation of the basic elements of language policy referenced by the title (language practices, ideology, and language management). Two approaches in modern education – the so-called monoglossic and heteroglossic approach – which reflect certain ideology about language teaching methods, are described in the second section. The third section provides insight into Content and Language Integrated Learning (CLIL) and the realization of this method in Latvia, while the fourth details the planning and practice of “Regional Studies” as a subject of study from the perspective of the heteroglossic approach. The fifth chapter outlines the experience of multilingual education in the European context, analyzing language education policies in the province of Friesland.The questions raised in the article have been evaluated in practice by: 1) preparing a publication on the CLIL approach internationally and in Latvia, and cooperating with teachers in all Latvian regions who utilize this approach in their schools; 2) leading teacher training courses on the use of digital tools in the teaching of Regional Studies and other subjects (conducted in Rēzekne in March and April of 2015); 3) collecting evidence from trilingual schools in the Dutch province of Friesland (lessons in six schools were observed in October 2015; additionally, interviews were conducted with teachers, schoolchildren and principals).In Latvian schools, both the monoglossic and heteroglossic approaches are observable. However, these different approaches are not mutually exclusive; rather, they exist on a continuum. It is recommended that schools in Latvia be given greater autonomy to choose their own language policies, in a similar fashion to the Frisian schools previously described in the ethnographic observations; this is not to speak against state language policy, but merely to highlight a need for school language policy to reflect regional specifics and context.